METODE KEṢAHĪHAN HADIS SUNNĪ VS METODE KEṢAHĪHAN HADIS SHĪ’AH - Muttaqin, Khairul (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2017)
Recently, there are two groups that always contradict in terms of ideology and methodology, namely Sunni and Shi’ah. In hadith terminology, those groups have different views. The validity method of prophet’s hadith by sunni is really different with the validity method of prophet’s hadith by shi’ah. The method used in this study is library research in which the writer investigates works related to the difference of methodologies between Sunni and Shi’ah in determining the validity of hadith. In matan and sanad hadith criticisms, there is significant difference between the both groups. The different ways make the difference in the validity of hadith and madhhab fiqh. Keywords: method, validity, Hadith, Sunni, Shi’ah